A Multifunctional Monooxygenase XanO4 Catalyzes Xanthone Formation in Xantholipin Biosynthesis via a Cryptic Demethoxylation. Issue 4 (21st April 2016) - Kong, Lingxin; Zhang, Weike; Chooi, Yit Heng; Wang, Lu; Cao, Bo; Deng, Zixin; Chu, Yiwen; You, Delin
Summary: Xantholipin and several related polycyclic xanthone antibiotics feature a unique xanthone ring nucleus within a highly oxygenated, angular, fused hexacyclic system. In this study, we demonstrated that a flavin-dependent monooxygenase (FMO) XanO4 catalyzes the oxidative transformation of an anthraquinone to a xanthone system during the biosynthesis of xantholipin. In vitro isotopic labeling experiments showed that the reaction involves sequential insertion of two oxygen atoms, accompanied by an unexpected cryptic demethoxylation reaction. Moreover, characterizations of homologous FMOs of XanO4 suggested the generality of the XanO4-like-mediated reaction for the assembly of a xanthone ring in the biosynthesis of polycyclic xanthone antibiotics. These findings not only expand the repertoire of FMO activities but also reveal a novel mechanism for xanthone ring formation. Graphical Abstract: Highlights: XanO4 is a multifunctional flavin-containing monooxygenase XanO4 catalyzes the oxidative transformation of anthraquinone to xanthone Cryptic demethoxylation is essential for the formation of a xanthone ring XanO4-mediated reaction is general in polycyclic xanthone antibiotics Abstract : Kong et al. discovered an unusual multifunctional flavin-containing monooxygenase (FMO) XanO4 that transforms an anthraquinone intermediate to the xanthone system in xantholipin, a polycyclic xanthone antibiotic. The reaction is accompanied by a cryptic demethoxylation that is indispensable for xanthone formation. These findings expand the inventory of FMO-mediated reactions.